In Vitro Antimicrobial Susceptibilities of Streptococcus pneumoniae Clinical Isolates Obtained in Canada in 2002 - Powis, Jeff (American Society for Microbiology, 2004)
Empirical treatment is best guided by current surveillance of local resistance patterns. The goal of this study is to characterize the prevalence of antimicrobial nonsusceptibility within pneumococcal isolates from Canada. The Canadian Bacterial Surveillance Network is comprised of laboratories from across Canada. Laboratories collected a defined number of consecutive clinical and all sterile site isolates of S. pneumoniae in 2002. In vitro susceptibility testing was performed by broth microdilution with NCCLS guidelines. Rates of nonsusceptibility were compared to previously published reports from the same network. A total of 2,539 isolates were tested. Penicillin nonsusceptibility increased to 15% (8.5% intermediate, 6.5% resistant) compared to 12.4% in 2000 (P ≤ 0.025, χ(2)). Only 32 (1.3%) isolates had an amoxicillin MIC of ≥4 μg/ml and only 2 of 32 cerebrospinal fluid isolates had an intermediate susceptibility to ceftriaxone by meningeal interpretive criteria (MIC = 1 μg/ml). A total of 354 (13.9%) isolates were macrolide nonsusceptible (46.3% MLS(B), 56.7% M phenotype), increasing from 11.4% in 2000 (P ≤ 0.0075, χ(2)). Only 13 (<1%) isolates had a telithromycin MIC of >1 μg/ml. Ciprofloxacin nonsusceptibility (defined as an MIC of ≥4 μg/ml) increased to 2.7% compared to 1.4% in 2000 (P ≤ 0.0025, χ(2)) and was primarily found in persons ≥18 years old (98.5%). Nonsusceptibility to penicillin, macrolides, and fluoroquinolones is increasing in Canada. Nonsusceptibility to amoxicillin and ceftriaxone remains uncommon. Newer antimicrobials such as telithromycin and respiratory fluoroquinolones have excellent in vitro activity.